Rapamycin Augments the NMDA-Mediated TNF Suppression of MRSA-Stimulated RAW264.7 Murine Macrophages - Thomas Spentzas; Rebekah K. H. Shappley; Fabio Savorgnan; Elizabeth Meals; B. Keith English (International Journal of Inflammation)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) can stimulate massive cytokine release. Ketamine suppresses tumor necrosis factor (TNF) secretion by MRSA-stimulated RAW264.7 macrophages, and the mechanism likely involves N-methyl-D-aspartic acid (NMDA) receptor antagonism. The downstream effects of NMDA-mediated TNF suppression, specifically the PI3K/Akt and mTOR modulation, have not been described. Methods. RAW264.7 cells were stimulated for 18 hrs with 105 to 107 CFU/mL inocula of either of two prototypical community-acquired- (CA-) MRSA isolates, USA300 strain LAC and USA400 strain MW2. Then we added the NMDA inhibitors ketamine or 2R-amino-5-phosphonopentanoate (AP5), NMDA substrate, LY294002, and rapamycin in various combinations. Results. NMDA inhibition suppressed TNF secretion by almost a third compared to the no-ketamine control. When NMDA substrate was added, the TNF secretion increased by 10%. Addition of LY294002 suppressed TNF production by macrophages by 20%. Rapamycin exhibited a concentration-dependent TNF induction-suppression response: induction at doses of 0.1 and 1 ng/mL and suppression at 10 and 100 ng/mL. Induction of TNF was abolished when LY294002 was added and the suppression became uniform. Ketamine-induced suppression of TNF secretion was intensified 10–15% when rapamycin was added, but not when LY294002 was added. Conclusion. These findings suggest that NMDA-induced TNF suppression can be augmented by concurrent mTOR inhibition.